Nitrogen Removal Improvement by Adding Peat in Deep Soil of Subsurface Wastewater Infiltration System - Pei-zhen CHEN; Jian-yu CUI; Lin HU; Miao-zhuang ZHENG; Shan-ping CHENG; Jie-wen HUANG; Kang-guo MU (Journal of Integrative Agriculture)
In order to enhance the nitrogen removal, a subsurface wastewater infiltration system (SWIS) was improved by adding peat in deep soil as carbon source for denitrification process. The effects of addition of carbon source in the underpart of the SWIS on nitrogen removal at different influents (with the total nitrogen (TN) concentration 40 and 80 mg L−1, respectively) were investigated by soil column simulating experiments. When the relatively light pollution influent with 40 mg L−1 TN was used, the average concentrations of NO3−-N and TN in effluents were (4.69±0.235), (6.18±0.079) mg L−1, respectively, decreased by 32 and 30.8% than the control; the NO3−-N concentration of all effluents was below the maximum contaminant level of 10 mg L−1; as high as 92.67% of the TN removal efficiency was achieved. When relatively heavy pollution influent with 80 mg L−1 TN was used, the average concentrations of NO3−-N and TN in effluents were (10.2±0.265), (12.5±0.148) mg L−1 respectively, decreased by 20 and 21.2% than the control; the NO3−-N concentration of all effluents met the grade III of the national quality standard for ground water of China (GB/T 14848-1993) with the values less than 20 mg L−1; the TN removal efficiency of 94.1% was achieved. In summary, adding peat in the underpart of the SWIS significantly decreased TN and NO3−-N concentration in effluents and the nitrogen removal efficiency improved significantly.